Assessment of psychological, cognitive parameters and sleep quality in newly diagnosed patients with Parkinson’s disease - Anitha Lakshmi,; Venkatesha R,; Doreswamy Kanakaiah,; Yashica Gowda R,; Sai Sailesh Kumar Goothy,; Mukkadan JK,; Sadgunothama Goud Kamparaj, (Asian Journal of Medical Sciences, 2024)
Background: Parkinson’s disease is a neurodegenerative disorder that occurs due to the damage of the neurons that secrete the neurotransmitter called dopamine and the cases are growing worldwide. The studies on the observation of the non-motor symptoms in patients with Parkinson’s disease are sparse in the Indian context. The estimated prevalence of Parkinson’s disease in India is 7 million. Aims and Objectives: The present study was undertaken to assess the psychological and cognitive parameters and sleep quality in newly diagnosed patients with Parkinson’s disease. Materials and Methods: A total of 30 newly diagnosed patients within the age group of 35–70 years, with Parkinson’s disease were part of the study after obtaining the informed consent. Thirty age and gender-matched healthy participants were also part of the study. Cognitive parameters were recorded using spatial and verbal memory tests. The psychological parameters were collected using the generalized anxiety disorder seven questionnaires which is a self-administered questionnaire. Sleep quality was assessed using an insomnia severity questionnaire which is a seven-item questionnaire. Results: The anxiety scores were significantly high in the patients with Parkinson’s disease when compared with the controls. The sleep quality was significantly poor in the Parkinson’s patients compared to the controls. Spatial and verbal memory scores were significantly lower in Parkinson’s patients than in the controls. Conclusion: The present study results support that the non-motor symptoms are also prominent in patients with Parkinson’s disease. Higher scores of anxiety, lower scores of spatial and verbal memory, and poor sleep quality were observed in patients with Parkinson’s disease. The study recommends further detailed studies in this area to consider these parameters also in managing Parkinson’s disease.